2016
DOI: 10.15252/msb.20156701
|View full text |Cite
|
Sign up to set email alerts
|

Predictive features of ligand‐specific signaling through the estrogen receptor

Abstract: Some estrogen receptor‐α (ERα)‐targeted breast cancer therapies such as tamoxifen have tissue‐selective or cell‐specific activities, while others have similar activities in different cell types. To identify biophysical determinants of cell‐specific signaling and breast cancer cell proliferation, we synthesized 241 ERα ligands based on 19 chemical scaffolds, and compared ligand response using quantitative bioassays for canonical ERα activities and X‐ray crystallography. Ligands that regulate the dynamics and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 49 publications
0
60
0
Order By: Relevance
“…Other side chain design strategies could be evaluated, as could the optimal matching between antiestrogen side chains and core structural elements, with the goal of optimizing affinity, potency, and antiproliferative efficacy, while also seeking the best pharmacokinetic behavior. There are even alternative approaches to disrupting the ERα agonist conformation by indirect mechanisms using ligands with expanded core elements (even ones without side chains) that distort the positioning of regions within the ligand-binding pocket that are needed to support the agonist conformation of helix 12 50,101103 . Finally, it will also be important to clarify the necessity—or even the desirability—of coupling ERα antagonism with ERα degradation (SERD activity), and determine whether ERα levels of both WT and mutant ERs can be lowered sufficiently to afford broad suppression of breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other side chain design strategies could be evaluated, as could the optimal matching between antiestrogen side chains and core structural elements, with the goal of optimizing affinity, potency, and antiproliferative efficacy, while also seeking the best pharmacokinetic behavior. There are even alternative approaches to disrupting the ERα agonist conformation by indirect mechanisms using ligands with expanded core elements (even ones without side chains) that distort the positioning of regions within the ligand-binding pocket that are needed to support the agonist conformation of helix 12 50,101103 . Finally, it will also be important to clarify the necessity—or even the desirability—of coupling ERα antagonism with ERα degradation (SERD activity), and determine whether ERα levels of both WT and mutant ERs can be lowered sufficiently to afford broad suppression of breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The growing corpus of crystal structures obtained for the Y537S mutant clearly shows that h12 is in the agonist conformation 16,45,49,50 , even without bound ligand 45 . The hydrogen bonding partner of S537 in the Y537S mutant is D351 on h3, and this tight interaction appears to be “latching the h11–12 spring” in the agonist conformation, turning on constitutive activity.…”
Section: [Introduction]mentioning
confidence: 99%
“…We also recently reported a meta-analysis of 241 compounds from 19 different scaffolds that included the OBHS-N compounds 25 , and used linear regression to identify which ERα-mediated signal transduction features predicted the proliferative response to the ligands. For some scaffolds, the induction of GREB1 mRNA and recruitment of SRC3 in the mammalian 2-hybrid assay predicted the proliferative response.…”
Section: Modulation Of Erα Degradationmentioning
confidence: 99%
“…For some scaffolds, the induction of GREB1 mRNA and recruitment of SRC3 in the mammalian 2-hybrid assay predicted the proliferative response. OBHS-N compounds showed the strongest predictions, and over 90% of their anti-proliferative effect was explained by SRC3 recruitment (r 2 = 0.92) and induction of GREB1 (r 2 = 0.92) 25 . Here we found that MYC expression also strongly predicted their proliferative effects on MCF-7 cells (r 2 = 0.73, p = 0.0002, F test for non-zero slope)(Supplementary Fig.…”
Section: Modulation Of Erα Degradationmentioning
confidence: 99%
See 1 more Smart Citation